Respuesta :

Space

Answer:

x = 1

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Step-by-step explanation:

Step 1: Define Equation

3(4x - 5) - 4x + 1 = -6

Step 2: Solve for x

  1. Distribute 3:                    12x - 15 - 4x + 1 = -6
  2. Combine like terms:       8x - 14 = -6
  3. Isolate x term:                 8x = 8
  4. Isolate x:                          x = 1

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x:                    3(4(1) - 5) - 4(1) + 1 = -6
  2. Multiply:                               3(4 - 5) - 4 + 1 = -6
  3. Subtract:                              3(-1) - 4 + 1 = -6
  4. Multiply:                               -3 - 4 + 1 = -6
  5. Subtract:                              -7 + 1 = -6
  6. Add:                                     -6 = -6

Here we see that -6 does indeed equal -6.

∴ x = 1 is the solution to the equation.